Patrones de distribución de escarabajos coprófagos (coleoptera: scarabaeidae) en relicto del bosque altoandino, cordillera oriental de Colombia (1997)
This study documents the diversity and distribution patterns of dung beetles in three relictual patches of montane forest located near the Sabana de Bogotá. 2486 individuals of 11 species in 6 genera were collected. The most abundant specie was Ontherus brevicollis, collected in two patches, followed by Dichotomius achamas collected in all three patches and Uroxys sp present only in one. Chicaque has the highest species richness with 10 species. We found a clear pattern related to habitat preferences, summarized in 3 groups: pasture beetles, edges and forest interior beetles.